Statistical approach in solving for initial and eventual wire bonding problem - Somasundram, Suresh Kumar (2013)
The project scope is related to solve the real life Semiconductor industrial problem.Interconnection processis identifiedas the most critical process among others compared to overall flow in Semiconductor Packaging. In semiconductor manufacturing industries, ball bonding and wedge bonding techniques are commonly adopted in the thermo compression (TIC) and thermo sonic (T/S) processes. Approximately 95% of aJI semiconductor packages are produced by applying the ball bonding method, while wedge ' bonding is applied to produce about 5% of all assembled packages. The research study has proven the ability to have robust process with optimum probe touchdown for the initial and good wire properties selection for the eventual bonding. Two years research effort covering a complete wire bondcycle involving both Initial and Eventual bonding top defective rate. As shown in the research all the aspects have been completed to derive comprehensive conclusion in-terms of material, method with support of statistical approach, the results of this research has gain good yield performance by reducing 50% of defective rate (Please refer to published papers) satisfying respective industry.